Professional Behavior And Public Morality To Confront And Reduce The Phenomenon Of Administrative Corruption In Algeria (Revue El-Wahat pour les Recherches et les Etudes, 2022)
abstract:This study aims to reveal the importance of the ethical side in addressing administrative corruption, especially the spread of this phenomenon at all administrative levels and its access to prejudice the economy of countries and peoples, which obliged governments and societies to move to find the mechanisms and procedures necessary to address the phenomenon of corruption in general and administrative corruption in particular in order to achieve the public interest, and  looking forward to a developed society based on standards and work ethics within governmental organizations and departments within a comprehensive framework that governs human behavior in the performance of public office tasks. keywords:Administrative corruption, Ethical behavior, Profession ethics, Profession ethical codes.   ملخص:تهدف هذه الدراسة إلى ابراز أهمية الجانب الأخلاقي في التصدي للفساد الإداري، خاصة بانتشار هذه الظاهرة في كل المستويات الإدارية  ووصولها إلى المساس باقتصاد  الدول والشعوب، مما ألزم الحكومات والمجتمعات التحرك لإيجاد الآليات والإجراءات  اللازمة للتصدي لظاهرة الفساد بشكل عام والفساد الإداري على وجه الخصوص تحقيقا للمصلحة العامة، والتطلع إلى مجتمع متطوّر مبني على معايير  وأخلاقيات عمل داخل المنظمات والإدارات الحكومية في إطار شامل يحكم السلوك الإنساني في أداء مهام  الوظيفة العامة، وينظم العلاقة بين المسؤوليات الأخلاقية والالتزامات القانونية على شكل أسس وضوابط  مدونة لأخلاقيات مهنية تسيّر بيئة العمل.كلمات دالة : الفساد الإداري، السلوك الأخلاقي، أخلاقيات المهنة، مدونات أخلاقية المهنة.